2011
DOI: 10.1590/s1415-47572011000400024
|View full text |Cite
|
Sign up to set email alerts
|

Studies of micronuclei and other nuclear abnormalities in red blood cells of Colossoma macropomum exposed to methylmercury

Abstract: The frequencies of micronuclei (MN) and morphological nuclear abnormalities (NA) in erythrocytes in the peripheral blood of tambaqui (Colossoma macropomum), treated with 2 mg.L−1 methylmercury (MeHg), were analyzed. Two groups (nine specimens in each) were exposed to MeHg for different periods (group A - 24 h; group B - 120 h). A third group served as negative control (group C, untreated; n = 9). Although, when compared to the control group there were no significant differences in MN frequency in the treated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…The assay also specifically evaluates individual cells for the presence of NA which include binucleated cells, lobed, notched or blebbed (nuclear buds) nuclear membranes. The exact pathways leading to the induction of NA are less understood, but have also been used as indicators of exposure to mutagenic or genotoxic contaminants in numerous fish species [Baršiene et al, ; da Rocha et al, ]. A variety of chemicals such as PCBs, PAHs, heavy metals and pesticides [Al‐Sabt and Metcalfe, ; Bolognesi and Hayashi, ; Obiakor et al, ] and more recently CEC [Teles et al, ; Filby et al, ; Iturburu et al, ] have been linked to erythrocyte MN and NA induction in various fishes.…”
Section: Introductionmentioning
confidence: 99%
“…The assay also specifically evaluates individual cells for the presence of NA which include binucleated cells, lobed, notched or blebbed (nuclear buds) nuclear membranes. The exact pathways leading to the induction of NA are less understood, but have also been used as indicators of exposure to mutagenic or genotoxic contaminants in numerous fish species [Baršiene et al, ; da Rocha et al, ]. A variety of chemicals such as PCBs, PAHs, heavy metals and pesticides [Al‐Sabt and Metcalfe, ; Bolognesi and Hayashi, ; Obiakor et al, ] and more recently CEC [Teles et al, ; Filby et al, ; Iturburu et al, ] have been linked to erythrocyte MN and NA induction in various fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the value of micronuclei as biomarkers and fish as sentinel organisms (e.g., Andrade et al 2004;Ferraro et al 2004;Souza and Fontanetti 2006). In addition, studies on genotoxicity indicate that C. macropomum has potential as an experimental model for monitoring aquatic ecosystems (Chapadense et al 2009;Groff et al 2010;Rocha et al 2011). The frequency of micronuclei and morphological nuclear abnormalities are effective tools for analyzing the health status of fish (Noga 2000;Webb and Gagnon 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fish also used for the potential of mutagenic and carcinogenic study of pesticide contaminants present in aquatic [8][9][10][11].…”
Section:  Correspondence Addressmentioning
confidence: 99%